Respuesta :

Answer:

1) Simplify the following:-

a)5⁴⁺⁶=5¹⁰

b)2⁷⁺¹=2⁸

c)6⁵⁻²=

d)9⁷⁻⁶=

2) Simplify the following:-

a)3²⁺⁴=3⁶

b)5⁷⁺³=5¹⁰

c)6⁷⁻²=6⁵

d)9⁴⁻³=

Answer:

see explanation

Step-by-step explanation:

using the rules of exponents

[tex]a^{m}[/tex] × [tex]a^{n}[/tex] = [tex]a^{(m+n)}[/tex]

[tex]a^{m}[/tex] ÷ [tex]a^{n}[/tex] = [tex]a^{(m-n)}[/tex]

Then

(a)

[tex]5^{4}[/tex] × [tex]5^{5}[/tex] = [tex]5^{(4+5)}[/tex] = [tex]5^{9}[/tex]

(b)

[tex]2^{7}[/tex] × 2 = [tex]2^{(7+1)}[/tex] = [tex]2^{8}[/tex]

(c)

[tex]6^{5}[/tex] ÷ 6² = [tex]6^{(5-2)}[/tex] = 6³

(d)

[tex]9^{7}[/tex] ÷ [tex]9^{6}[/tex] = [tex]9^{(7-6)}[/tex] = [tex]9^{1}[/tex] = 9

------------------------------------------------

(a)

3² × [tex]3^{4}[/tex] = [tex]3^{(2+4)}[/tex] = [tex]3^{6}[/tex]

(b)

[tex]5^{7}[/tex] × 5³ = [tex]5^{(7+3)}[/tex] = [tex]5^{10}[/tex]

(c)

[tex]6^{7}[/tex] ÷ 6² = [tex]6^{(7-2)}[/tex] = [tex]6^{5}[/tex]

(d)

[tex]9^{4}[/tex] ÷ 9³ = [tex]9^{(4-3)}[/tex] = [tex]9^{1}[/tex] = 9

ACCESS MORE